Screening transcriptional connections in Staphylococcus aureus using high-throughput transduction of bioluminescent reporter plasmids. Issue 4 (21st April 2022) - Weiss, Andy; Jackson, Jessica K.; Shaw, Lindsey N.; Skaar, Eric P.
Abstract : Characterization of transcriptional networks is one of the main strategies used to understand how bacteria interact with their environment. To reveal novel regulatory elements in the human pathogen Staphylococcus aureus, we adapted a traditional transduction protocol to be used in a high-throughput format in combination with the publicly available S. aureus Nebraska Transposon Mutant Library. Specifically, plasmid transductions are performed in 96-well format, so that a single plasmid can be simultaneously transferred into numerous recipient strains. When used in conjunction with bioluminescent reporter constructs, this strategy enables parallel and continuous monitoring of downstream transcriptional effects of hundreds of defined mutations. Here, we use this workflow in a proof-of-concept study to identify novel regulators of the staphylococcal metalloprotease aureolysin. Importantly, this strategy can be utilized with any other bacterium where plasmid transduction is possible, making it a versatile and efficient tool to probe transcriptional regulatory connections.